2016
DOI: 10.21742/ijaner.2016.1.12
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship among Personality, Interpersonal Relations and Stress of Clinical Practice of Nursing Students

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The results of hierarchical regression analysis showed personality dimensions which were entered in firs step for predicting of clinical clerkship satisfaction in nursing students had a significant role; among five factors of personality, only extraversion predicted satisfaction with clinical clerkship of intern nursing students. Considering the definition of extraversion [13], students who were sociable, others lover and enjoyed talking to patients and also, those who had a tendency to acquire various experiences from their clinical practice, were more satisfied with their clinical clerkship [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…The results of hierarchical regression analysis showed personality dimensions which were entered in firs step for predicting of clinical clerkship satisfaction in nursing students had a significant role; among five factors of personality, only extraversion predicted satisfaction with clinical clerkship of intern nursing students. Considering the definition of extraversion [13], students who were sociable, others lover and enjoyed talking to patients and also, those who had a tendency to acquire various experiences from their clinical practice, were more satisfied with their clinical clerkship [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Getting the best and fastest health care with maximum safety is the right of every human being (50) and the nurse is at the forefront of providing these services in hospitals. In this regard, suitable communication along with adequate knowledge and a healthy personality are of the most important tools for professional and modern nursing (18). This study also had limitations.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, the neuroticism personality dimension was a negative predictor of perception of verbal and nonverbal messages and emotional regulation (16). In two other studies, the researchers reported that there was a positive and significant relationship between personality traits and communication skills (17,18). Therefore, investigation of personality traits of nurses is of particular importance and is taken into account as an important factor in demonstrating their ability to provide patient care services for patients and their resilience in the hospital environment.…”
Section: Introductionmentioning
confidence: 99%
“…Among the ve factors of personality, only extraversion predicted satisfaction with clinical clerkship of intern nursing students. Considering the de nition of extraversion [13], students who were sociable, others' lover and enjoyed talking to patients and also, those who had a tendency to acquire various experiences from their clinical practice, were more satis ed with their clinical clerkship [44,45]. Nurses who are more extroverted are more likely to participate in teamwork and solve problems with the help of their colleagues.…”
Section: Discussionmentioning
confidence: 99%